Real-World Evidence Study on the Long-Term Safety of Everolimus in Patients With Tuberous Sclerosis Complex: Final Analysis Results - Ruiz-Falcó Rojas, María Luz; Feucht, Martha; Macaya, Alfons; Wilken, Bernd; Hahn, Andreas; Maamari, Ricardo; Hirschberg, Yulia; Ridolfi, Antonia; Kingswood, John Chris (Frontiers in Pharmacology, 2022)
The TuberOus SClerosis registry to increase disease Awareness (TOSCA) Post-Authorization Safety Study (PASS) was a non-interventional, multicenter, safety substudy that assessed the long-term safety of everolimus in patients with tuberous sclerosis complex (TSC) receiving everolimus for its licensed indications in the European Union (EU). This substudy also aimed to address TSC-associated neuropsychiatric disorders (TAND), sexual development, and male infertility. Eligible patients were enrolled from 39 sites across 11 countries in the EU. Outcomes of interest included the incidence of adverse events (AEs), serious adverse events (SAEs), treatment-related AEs (TRAEs), AEs leading to everolimus discontinuation, AEs of special interest (AESIs), the observed relationship between everolimus blood levels and incidence of AESIs, TAND, and reproductive clinical features. Herein, we present the final analysis results from this substudy (data cutoff date: January 22, 2020). At data cutoff, 179 patients were enrolled (female, 59.2%; age ≥18 years, 65.9%), of which the majority completed the study (76%). Overall, 121 patients (67.6%) had AEs regardless of causality. The most frequent TRAEs (≥5%) were stomatitis (7.8%), aphthous ulcer (6.7%), and hypercholesterolemia (6.1%). The most common treatment-related SAEs (>1%) were pneumonia (3.4%), influenza, pyelonephritis, aphthous ulcer, stomatitis, dyslipidemia, and hypercholesterolemia (1.1% each). Ten patients (5.6%) reported AEs leading to everolimus discontinuation. The common psychiatric disorders (N=179) were autism spectrum disorder (21.8%), anxiety disorder (12.8%), “other” psychiatric disorders (8.9%), attention-deficit hyperactivity disorder, and depressive disorder (7.8% each). Of 179 patients, 88 (49.2%) had ≥1 behavioral problem. Of these (n=88), the most common (>20%) were sleep difficulties (47.7%), anxiety (43.2%), mood swings (37.5%), depression mood (35.2%), impulsivity (30.7%), severe aggression (23.9%), and overactivity (22.7%). Of 179 patients, four (2.2%) reported abnormal puberty onset, and three (1.7%) reported other reproductive disorders. Of 106 females, 23 (21.7%) reported menstrual cycle disorders and 10 (9.4%) reported amenorrhea. Available data did not show delays in sexual maturation or an association between sexual development and infertility. The results demonstrate that everolimus has a manageable long-term safety profile in the TSC treatment setting. No new safety signals emerged. This substudy also contributed to the mapping of TAND and reproductive clinical features in patients with TSC.